2014
DOI: 10.1039/c4cp01285b
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impedance response of mixed-conducting thin film electrodes

Abstract: In this paper a novel numerical impedance model is developed for mixed-conducting thin films working as electrodes for solid oxide fuel cells. The relative importance of interfaces is considered by incorporating double layer contributions at the film/gas boundary. Simulations are performed on a model system, namely doped ceria, in a symmetric cell configuration using geometrically well-defined patterned metal current collectors. Results reveal that experimentally consistent bulk impedances and surface capacita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
2
20
0
1
Order By: Relevance
“…The individual contribution of each resistive step to the total electrode resistance M A N U S C R I P T is given in Table 3. Inline with the previous studies [13,12], the resistance caused by the ionic and the electronic transport is significantly smaller than the resistance caused by the surface kinetics. This implies that the diffusion process is fast enough to be unlikely to control the cell response at these conditions.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The individual contribution of each resistive step to the total electrode resistance M A N U S C R I P T is given in Table 3. Inline with the previous studies [13,12], the resistance caused by the ionic and the electronic transport is significantly smaller than the resistance caused by the surface kinetics. This implies that the diffusion process is fast enough to be unlikely to control the cell response at these conditions.…”
Section: Resultssupporting
confidence: 85%
“…Since the resistance caused by the bulk transport is insignificant compared to the resistance caused by the reaction kinetics, rate limitations are globally attributed to the surface kinetics that is in line with the previous studies [13,12,30]. The kinetics of elementary steps in the proposed reaction scheme allow us to identify the rate-determining elementary step, which is performed by a sensitivity analysis.…”
Section: Rate-determining Stepsupporting
confidence: 71%
See 1 more Smart Citation
“…39 Those studies revealed that such model type experiments based on MIEC thin films and current collectors are highly valuable in order to better understand properties and limitations of mixed conducting SOFC anodes /SOEC cathodes. However, mechanistic studies on LSF thin film electrodes in H 2 /H 2 O are rare, one study reports its performance in a SOEC cell.…”
Section: F318mentioning
confidence: 99%
“…COMSOL Multiphysics software, a complex simulation program, can be applied to model electrochemical analysis [16]. There are many successful modeling studies reported in recent years with COMSOL [17,18]. However, there are few COMSOL modeling studies for electrodeposition of coatings [19,20].…”
Section: Introductionmentioning
confidence: 99%